2004
DOI: 10.1111/j.0301-5661.2004.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood caries in children aged 6–19 months

Abstract: ECC is not only a public health problem but also a social problem in Thailand, because it relates to family income and education level. The community development approach to assisting disadvantaged Thai children should be combined with an effective preventive program at a very young age. Future longitudinal research should be performed to improve the I-ECC for measuring the severity of ECC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
82
2
23

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 21 publications
15
82
2
23
Order By: Relevance
“…Its etiology is complex and results from the interaction of several factors, such as: high consumption of fermentable carbohydrates, negligence in oral hygiene, low family socioeconomic status, and mother's limited educational level (20)(21)(22)(23) . This work showed that, when it comes to babies' oral hygiene, the education interventions of the above mentioned program were able to generate self-care skills in the mothers involved in the study and to stimulate healthy habits in their children (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Its etiology is complex and results from the interaction of several factors, such as: high consumption of fermentable carbohydrates, negligence in oral hygiene, low family socioeconomic status, and mother's limited educational level (20)(21)(22)(23) . This work showed that, when it comes to babies' oral hygiene, the education interventions of the above mentioned program were able to generate self-care skills in the mothers involved in the study and to stimulate healthy habits in their children (13) .…”
Section: Discussionmentioning
confidence: 99%
“…mothers, 39 of parents with low educational level, especially of illiterate mothers. 7,26,28,33,37,39,40 In this population, prenatal and perinatal malnutrition or undernourishment are the cause of enamel hypoplasia; oral hygiene is usually poor; exposure to fluorine is probably insufficient 12,39 and there is a greater preference for sugary foods. 36,41 Several diseases are associated with ECC, among them, malnutrition, 9,24,34,35,42 asthma, recurrent infections, chronic diseases, in addition to medication use.…”
Section: Susceptible Hostmentioning
confidence: 99%
“…ECC is more commonly found in children who live in poverty or in poor economic conditions, 7,11,[24][25][26][33][34][35][36][37] who belong to ethnical and racial minorities, 12,38 born to single Although the habit of dipping the pacifier in sugar is associated with early colonization by Streptococcus mutans in predentate infants, 49 a systematic review did not find any consistent correlation between the use of pacifiers and the development of ECC, regardless of the length of use of pacifiers and of the introduction of sweeteners or not. 50 Cariogenic role of human milk, cow s milk and milk-based formulas in infant feeding…”
Section: Associated Risk Factorsmentioning
confidence: 99%
“…Whilst few studies reported that this association has not been established and requires further epidemiological research with strong design and analysis to prove this fact [47][48][49]. The early childhood caries burden varies among different communities and it is found high in disadvantaged and underprivileged communities [50][51][52][53][54][55][56][57]. The snacking habit found different in low and high income groups.…”
Section: Role Of Mothers In Prevention Of Early Childhood Caries and mentioning
confidence: 99%